1985
DOI: 10.3109/01674828509085267
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Gender to Perceived Stress and Distress in Medical School

Abstract: This study focused on gender differences in perceived stress and distress in response to the pre-clinical years of medical school. Females (N = 248) reported significantly more anxiety than males (N = 345); however, the 2 groups reported similar levels of depression and self-esteem. Females had significantly higher scores than males on such perceived stressors as: isolation in the school environment, faculty hostility, administrative obstacles, and expectations about enduring the demanding role of the physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
1
6
0
2
Order By: Relevance
“…They also reported a finding that suicide attempts of college students generally happen more often among adolescents with above-average grades and who attend highly competitive schools. Russo, Miller, and Vitaliano (1985) reported that the suicide rates are 3 times higher among female medical students and physicians than in the general female population. A study of gifted and nongifted Australian adolescents showed that gifted girls reported overall lower self-esteem than did their nongifted peers (Lea-Wood & Clunies-Ross, 1995).…”
Section: Population Characteristicsmentioning
confidence: 99%
“…They also reported a finding that suicide attempts of college students generally happen more often among adolescents with above-average grades and who attend highly competitive schools. Russo, Miller, and Vitaliano (1985) reported that the suicide rates are 3 times higher among female medical students and physicians than in the general female population. A study of gifted and nongifted Australian adolescents showed that gifted girls reported overall lower self-esteem than did their nongifted peers (Lea-Wood & Clunies-Ross, 1995).…”
Section: Population Characteristicsmentioning
confidence: 99%
“…여러 연구에서 의과대학생들은 주로 엄 청난 학습량, 시험 및 성적관리, 여가시간의 부족, 가 족과 친구와의 교류시간 부족, 그리고 학습내용의 난 이도 등으로 인해 스트레스를 경험하는 것으로 보고 된 바 있는데 (Linn & Zeppa, 1984;Lloyd & Gartrell, 1983;Niemi & Vainiomaki, 1999;Saipanish, 2003), 이중에서도 스트레스 요인의 80% 이상이 학업과 관 련한 것으로 Guthrie et al (1995) (Baker, 2003(Baker, , 2004Fortier, et al, 1995), Baker, 2004;Vallerand & O'Connor, 1989). 이러한 무동기적 특성은 남학생들이 여학생들에 비해 높은 것 으로 몇몇 연구 (Sobral, 2004;Vallerand et al, 1989 그러나 본 연구 결과는 몇몇 다른 연구 결과들 (Clark & Rieker, 1986;Dahlin et al, 2005;Lloyd & Garrell, 1983;Russo et al, 1985;Toews et al, 1997 …”
unclassified
“…They conclude, women in the 30 to 39-year age group are exposed to high stress and are thus a vulnerable group (Bergdahl & Bergdahl, 2002). Similarly, the findings of Russo, Miller and Vitaliano (1985) indicate females had substantially higher scores than males on such perceived stressors as: isolation in the academic surrounding, faculty hostility, regulatory interferences, and expectations about facing the challenging role of the physician. Females also reported more syndromes of depression in response to stressors concerning the school atmosphere.…”
Section: Literature Reviewmentioning
confidence: 55%
“…Females also reported more syndromes of depression in response to stressors concerning the school atmosphere. These results underline anecdotal papers which have conferred the primary difficulties females have in a male-oriented medical surrounding (Russo, Miller, & Vitaliano, 1985). Bernard Misigo (2015) investigated the influence of Gender on perceived stress level of undergraduate university students from three public universities in the western part of Kenya and found a significant difference between the stress mean scores of males and females (Misigo, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%